GEOCHEMISTRY AND GENETIC IMPLICATIONS OF BASEMENT ROCKS AROUND MAKARFI AREA, NORTHWESTERN NIGERIA BASEMENT COMPLEX - Hayatu, Raliya Aminu (FUDMA Journal of Sciences, 2024)
Major and trace element analysis of rocks around Makarfi were carried out using Inductively Coupled Plasma Mass Spectrometry (ICP-MS) to determine the geochemical characteristics of the lithological components of the area. The area is composed of migmatite gneiss, biotite gneiss, granite gneiss, schists and granites. Analysis for major, trace and REE revealed that the gneisses, are paragneisses and metaluminous. The granites are peraluminous (A/CNK>1) and calc-alkaline. The granites had undergone changes from a more primitive hornblende-biotite I-type variety to a more fractionated muscovite bearing S-type variety. Chemical data shows that the peraluminosity and enrichment in Li, Rb, Cs, Ta, Sn, Nb and Ga increases in the course of differentiation and evolution from hornblende-biotite granite to muscovite granite. Signatures of biotite and muscovite granites suggest emplacement in a syn-collisional tectonic setting while those of hornblende-biotite granite suggest a post-collisional tectonic setting.
Keywords: Peraluminous; Metaluminous; Calc-alkaline; Paragneisses; Syn-collisional; Post-collisional